An adaptive LBER-Rake receiver for UWB system - Chung, Gwo Chin; Alias, Mohamad Yusoff; Chuah, Teong Chee (The Institute of Electronics, Information and Communication Engineers, 2008)
One of the major issues in ultra wideband (UWB) communications is the need to resolve multipaths and eliminate severe intersymbol interference (ISI). Although the conventional Rake can achieve multipath diversity for the desired signals, it does not mitigate ISI. We propose an adaptive Rake receiver by introducing the least bit error rate (LBER) criterion into the design of its finger coefficients. Results show that the proposed receiver achieves better performance than the conventional Rake receiver and the minimum mean square error (MMSE)-Rake receiver at high data rate.